DETERMINANTS ANALYSIS OF BEHAVIORAL INTENTION AND USE BEHAVIOR OF THE NEW SAKPOLE APPLICATION, USING THE UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY 2 (UTAUT2) MODEL - Aisah, Siti; Handoyono, Rudi; Farizi, Musyafa Al (KEUNIS, 2024)
Sakpole is a motor vehicle tax payment system for taxpayers in Central Java Province. This study aims to analyze the factors that affect the "New Sakpole" Application's behavioural intention and use behaviour using the UTAUT2 Model involving the perceived security aspect. This type of research is a quantitative approach, through distributing questionnaires using purposive sampling techniques, with a research sample of 409 respondents as vehicle taxpayers in the Semarang coordinator's UPPD. The data were analyzed using Smart PLS 3 Software. The findings indicated that the intention to use the "New Sakpole" application was shaped by several factors: performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and perceived security. The actual usage of the "New Sakpole" application was driven by facilitating conditions and behavioural intention. Additionally, age and gender served as moderator variables, impacting the relationships between these factors as evidenced by changes in the t-statistics value.